2002
DOI: 10.1002/1616-3028(20020517)12:5<359::aid-adfm359>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

[Cp*W(dmit)2]•: An Organometallic 15-Electron Neutral Radical (d1) with Optical Limiting Properties in Solution and an Antiferromagnetic Ground State in the Solid State

Abstract: The synthesis of the organometallic d2 [Cp*W(dmit)2]1– complex (where Cp* is pentamethylcyclopentadienyl and dmit is 1,3‐dithiole‐2‐thione‐4,5‐dithiolate), and its oxidation to the paramagnetic d1 [Cp*W(dmit)2]• species, is described and their X‐ray crystal structures given. Geometrical evolutions upon oxidation, characterized by a variable folding of the WS2C2 metallacycles along the S–S hinge, are rationalized by density functional theory (DFT) calculations and by comparison with the molybdenum analogs; as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…Fourmigué et al already reported the Cp * M bisdithiolene complexes [Cp * M(dmit) 2 ] n (M = Mo [10] and W [28]; n = À1 and 0). According to their articles, when the complex is the monoanion [Cp * M(dmit) 2 ] À (M = d 2 metal), two metalladithiolene rings are planar, however, in the neutral complex [Cp * M(dmit) 2 ] 0 (M = d 1 metal), one of the two metalladithiolene rings is distorted.…”
Section: X-ray Structures Of Molybdenum Dithiolene Complexesmentioning
confidence: 43%
“…Fourmigué et al already reported the Cp * M bisdithiolene complexes [Cp * M(dmit) 2 ] n (M = Mo [10] and W [28]; n = À1 and 0). According to their articles, when the complex is the monoanion [Cp * M(dmit) 2 ] À (M = d 2 metal), two metalladithiolene rings are planar, however, in the neutral complex [Cp * M(dmit) 2 ] 0 (M = d 1 metal), one of the two metalladithiolene rings is distorted.…”
Section: X-ray Structures Of Molybdenum Dithiolene Complexesmentioning
confidence: 43%
“…The reacted copper , ( 37 , Chart ) and tungsten or molybdenum ( 38a , b , Chart ) dithiolene complexes have also been tested for third-order optical nonlinearities. Complex 37 was tested by Z -scan technique with ps and ns laser pulses in the NIR region.…”
Section: Hybrid Organic–inorganic Materialsmentioning
confidence: 99%
“…TPA has been found when the sample solution was irradiated by 40 ps pulse width at 1064 nm and the TPA coefficient was 4 × 10 –13 m/W. , Upon excitation with 15 ns laser pulses at 1053 nm, the Z -scan profiles revealed strong RSA. The nonlinear absorption coefficient was found to be 7.07 × 10 –11 m/W. , On the other hand, complex 38a , along with complex 38b (Chart ), exhibited weak OL effect …”
Section: Hybrid Organic–inorganic Materialsmentioning
confidence: 99%
See 2 more Smart Citations